The role of political parties in political stability and lack thereof Kurdistan Region Iraq model - د. شڤان أحمد عبدالقادر; المدرسة المساعدة هاژە كۆسرةت مجيد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The research under the title "The role of political parties in the political stability and political instability of the Kurdistan Region of Iraq as a model) to show how the political parties have a role or influence on the process of political stability and political instability within the Kurdish society. It is worth mentioning that in the context of democratic transformation in the Kurdistan Region of Iraq, the importance of developing the role of political parties becomes an important and effective role in creating a social, economic and political life system in society. For this purpose, the researcher relied on more than two approaches to scientific research such as analytical and historical approach, analytical and descriptive approach, and case study. In light of the problematic nature of the research and its basic premises, the structure of the research was divided into three sections: The first is the general theoretical framework aimed at shedding light on the theoretical issues of the phenomenon of political parties and divided it into two requirements: The first requirement to deal with the co ncept of political parties was defined as a language and a formula. The second is to discuss the types of political parties and types of systems Party and party functions. In the second section, it was devoted to defining political stability by addressing the most important theoretical trends that contributed to defining its nature by dividing it into two requirements: The first requirement was devoted to clarifying indicators of political stability, and the second is to discuss the factors influencing the phenomenon of political stability The third and last topic: To enrich the research, we decided to attach to its theoretical and practical aspects this topic, in which we highlight the role of political parties on the phenomenon of political stability and political instability. The research was followed by a conclusion that includes the most important conclusions we reached, including: 1- Educating the Kurdish citizens about the negative effects of the problems and differences between the political parties operating in the Kurdistan Region of Iraq and the nonarrangement of the Kurdish House to achieve stability in various political, economic and social aspects through the various visual and audio media. 2. The problem of political instability in the Kurdistan Region of Iraq can not be dealt with through the necessary institutional reforms of the administrative and financial institutions of the State or regulatory bodies alone, but through the alliance of all organs, institutions and state authorities, including government agencies, regulators, the private sector and also civil society.